2008
DOI: 10.1016/s0076-6879(08)02627-x
|View full text |Cite
|
Sign up to set email alerts
|

Chapter 27 Cell Biology of mRNA Decay

Abstract: Studying single mRNA molecules has added new dimensions to our understanding of gene expression and the life cycle of mRNA in cells. Advances in microscopes and detection technology have opened access to single molecule research to most researchers interested in molecular biology. Here we provide an overview technique for single molecule studies of RNA in either fixed samples or in living cells. As part of a volume on mRNA turnover, it is increasingly relevant, because many of the recent advances in studies of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…To directly show the association of collagen mRNAs with vimentin filaments in vivo, we utilized RNA FISH. This method can detect single mRNA molecules in the cytoplasm (4,19,24,31,59). To visualize collagen mRNAs, we designed multiple short 50-mer oligonucleotide probes that specifically hybridize with their target mRNAs.…”
Section: Resultsmentioning
confidence: 99%
“…To directly show the association of collagen mRNAs with vimentin filaments in vivo, we utilized RNA FISH. This method can detect single mRNA molecules in the cytoplasm (4,19,24,31,59). To visualize collagen mRNAs, we designed multiple short 50-mer oligonucleotide probes that specifically hybridize with their target mRNAs.…”
Section: Resultsmentioning
confidence: 99%
“…A modified version of Robert Singer's laboratory protocol [23] was used. Oligonucleotide probes (50-nucleotides long) were designed using Vector NTI software (Invitrogen), and the probe specificity was verified with Ensembl BlastView tool.…”
Section: In Situ Hybridizationmentioning
confidence: 99%
“…Since the use of extensive washes to remove salts and formamide after the FISH procedure and before IF did not help, we chose the IF->FISH procedure as a more promising variant for further development. Our choice of IF followed by FISH was further supported by the protocol proposed by Grnwald et al (12), which we found partially successful but insufficient in terms of signal intensities, staining patterns, and the formation of secondary antibody artifactual speckles (discussed in detail below).…”
Section: Resultsmentioning
confidence: 55%